Risk Factor Analysis of Musculoskeletal Disorders (MSDS) in Women Shellfish Peelers - Syahadatina, Syahadatina (GLOBAL HEALTH SCIENCE GROUP, 2024)
The purpose of this study was to determine the possibility of women mussel fishermen in Tanjung Tiram District, Batubara Regency reporting musculoskeletal diseases. This study aims to determine work attitudes and possible complaints of musculoskeletal problems in women mussel peelers in Tanjung Tiram District, Coal Regency. The number of samples in this study was 45 women shellfish peeler respondents. This type of research uses case investigation methods and is quantitative. Data was collected through document analysis, in-depth interviews with six informants using NBM and REBA techniques, and observation. Using unibivariate and bivariate analysis tests. It is known that complaints fall into the low and medium categories based on the results of calculations carried out using the NBM method. Medium category work attitude, standing category work attitude, and high category hunched work attitude are the results of calculating sitting work attitude using the REBA strategy. The waist, neck, wrists, shoulders and calves are the areas of the body of workers most commonly affected by musculoskeletal diseases. Risk factors for bone disorder complaints include length of work, age, gender, work attitude, length of work, and anthropometry. Company owners and employees are required to rest and stretch when their bodies ache to reduce potential complaints.